Reforming public pensions : sharing the experiences of transition in OECD countries. (Emerging economies transition, 2004)
Reforms to pension policies inevitably face challenges and potential trade-offs. These include the desirability of providing adequate replacement income and tackling problems of poverty in old age; the imbalance between time spent in work and in retirement; the appropriate mix of different forms of retirement income provisions; the labour market implications of different approaches to financing pensions; and the potential complexities of meeting short-term and long-term policy objectives.